Correlation Analysis of Hardiness Personality to Work Motivation of Home Industry Employees - Wahyu Eko Prasetyo (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
The purpose of this study was to determine the relationship between the hardiness personality variables and work motivation in employees of home Industry. This is interesting because the majority of employees in home indrustiy have employees with different levels of education and characteristics from companies in general. This research is a quantitative research model with a correlational design, the population is taken as many as 89 people who are employees in one of the home industry production companies. Hypothesis testing in this study uses the Pearson (Product Moment) correlation technique which is aimed at determining the relationship between the independent variable (X) of hardiness personality and the dependent variable (Y) of work motivation. Based on the calculation of the analysis, r = 0.786 was obtained with sig = 0.000 < 0.050 which means that there is a positive relationship between personality hardiness and work motivation. Based on the results of determining the category of hardiness personality score information from 89 subjects, who had a hardiness personality with a low category of 12 employees or 13%, who had a medium hardiness personality of 47 employees or 53%, and who had a high hardiness personality of 30 employees or 34%. Meanwhile, based on the results of determining the category description of the work motivation score of 89 subjects, who had work motivation with a low category of 5 employees or 6%, who had moderate work motivation of 30 employees or 34%, who had high motivation of 40 employees or 45%, and who had very high work motivation of 14 employees or 16%. So that further research is expected to develop research designs to a wider format with much larger population size. The hope is that it will be able to bring up findings related to hardiness with work motivation in employees.